2016
DOI: 10.1080/21645698.2016.1138196
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-route monitoring and a comparative study of the occurrence of herbicide-resistant oilseed rape (Brassica napusL.) along a Japanese roadside

Abstract: Previously, we conducted a roadside survey to reveal the occurrence of genetically modified (GM) oilseed rape along a Japanese roadside (Route 51). In this study, we performed successive and thorough fixed-route monitoring in 5 sections along another road (Route 23). Oilseed rape plants were detected on both sides of the road in each section between autumn 2009 and winter 2013, which included 3 flowering seasons. In four sections, more plants were found on the side of the road leading from the Yokkaichi port t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…Survival of oilseed rape outside cultivation areas is possible. Demographic studies and surveys have shown the ability of oilseed rape (B. napus) to establish self-perpetuating populations outside agricultural areas, mainly in seminatural and ruderal habitats in different countries (reviewed by Devos et al, 2012;Bauer-Panskus et al, 2013;COGEM, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Busi and Powles, 2016;Nishizawa et al, 2016). oilseed rape is generally regarded as an opportunistic species, which can take advantage of disturbed sites (e.g.…”
Section: Potential Unintended Effects On Plant Fitness Due To the Genmentioning
confidence: 99%
“…Survival of oilseed rape outside cultivation areas is possible. Demographic studies and surveys have shown the ability of oilseed rape (B. napus) to establish self-perpetuating populations outside agricultural areas, mainly in seminatural and ruderal habitats in different countries (reviewed by Devos et al, 2012;Bauer-Panskus et al, 2013;COGEM, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Busi and Powles, 2016;Nishizawa et al, 2016). oilseed rape is generally regarded as an opportunistic species, which can take advantage of disturbed sites (e.g.…”
Section: Potential Unintended Effects On Plant Fitness Due To the Genmentioning
confidence: 99%
“…Other studies on gene flow from GM B. napus to non-GM B. rapa have been conducted in the United Kingdom and Japan (Warwick et al 2008;Aono et al 2011;Luijten et al 2015). Moreover, the seeds of GM B. napus with herbicide-resistant traits were found along the roadside and railway lines in Japan and Canada, and these spilled seeds survived and crossed with B. rapa relatives (Yoshimura et al 2006;Nishizawa et al 2016). Furthermore, the escapes of GM B. napus event GT73 were reported around the port area and railway in Switzerland, where no cultivation and importation of GM B. napus were allowed (Hecht et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The number of publications related to contamination by GM seeds and plant propagating material identified by the literature search was relatively small reflecting general lack of information on these issues. Most of the publications were related to GM grains imported for food and feed purposes, which may escape in the environment (Aono et al., 2011; Cowan, 2014; Devos et al., 2012; Gamarra et al., 2011; Goto et al., 2017; Han et al., 2015; Hanzer et al., 2012; Hecht et al., 2014; Yamaguchi et al., 2003; Kawata et al., 2009; Kim et al., 2006; Lamb and Booker, 2011; Macias-De Ia Cerda et al., 2012; Milcamps et al., 2009; Nikolic et al., 2010; Nishizawa et al., 2009; Nishizawa et al., 2016; Nishizawa et al., 2010; Park et al., 2010; Santa-Maria et al., 2014; Schoenenberger and D'Andrea, 2012; Schulze et al., 2015; Schulze et al., 2014; Serratos-Hernandez et al., 2007; Turkec et al., 2016a,b; Zdjelar et al., 2014). Majority of the cases of occurrence of GM seeds have been detected outside European Union, e.g., in Japan, Korea, Mexico or Argentina, and those have been linked to sites of seed import and transport routes.…”
Section: Main Textmentioning
confidence: 99%